Predictors of Outcome After Alcohol Septal Ablation for Hypertrophic Obstructive Cardiomyopathy: An Echocardiography and Cardiovascular Magnetic Resonance Imaging Study. (March 2016) - Lu, Minjie; Du, Hui; Gao, Zhan; Song, Lei; Cheng, Huaibing; Zhang, Yan; Yin, Gang; Chen, Xiuyu; Ling, Jian; Jiang, Yong; Wang, Hao; Li, Jinghui; et al.
Abstract : Background—: Alcohol septal ablation (ASA) is used for treatment of medically refractory hypertrophic obstructive cardiomyopathy patients with severe left ventricular outflow tract (LVOT) obstruction. The current recommendations restrict the procedure to adults with favorable anatomy and no other coexisting surgically amenable disease. Some patients remain symptomatic with residual LVOT obstruction, thus better patient selection is required. Methods and Results—: One-hundred and two consecutive subjects with hypertrophic obstructive cardiomyopathy who underwent cardiovascular magnetic resonance imaging, transthoracic echocardiography, and ASA were enrolled in this study. Successful ASA was defined as reduction of LVOT gradient ≥50% of baseline by echocardiographic follow-up 6 months post ASA. The relationships between segmental thickness assessed by cardiovascular magnetic resonance imaging and echocardiography and outcomes of ASA were compared between the 2 groups. The survival rate after ablation was 100% at 6-month follow-up. The LVOT gradient decreased ≥50% of baseline in 72% (73/102) patients. There were good correlations between the reduction of postoperative LVOT gradient and the thickness of basal anterior segment ( r =0.371; P <0.001), basal anteroseptal segment ( r =0.527; P <0.001), and total thickness of the above 2 segments ( r =0.672; P <0.001). The area under the receiver operating curves were 0.68, 0.79 and 0.89 for predictive analysis (all P <0.001). The cutoff thickness of the segment 1+2 was 50.9 mm, which yielded a sensitivity of 86% and specificity of 77%. Conclusions—: Both echocardiography and cardiovascular magnetic resonance imaging can be used effectively as noninvasive tools for patient selection for ASA procedure. A significantly thickened septum among hypertrophic obstructive cardiomyopathy patients may be associated with a poor outcome after ASA.